7x-3-6x=3

Simple and best practice solution for 7x-3-6x=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-3-6x=3 equation:


Simplifying
7x + -3 + -6x = 3

Reorder the terms:
-3 + 7x + -6x = 3

Combine like terms: 7x + -6x = 1x
-3 + 1x = 3

Solving
-3 + 1x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 1x = 3 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = 3 + 3
1x = 3 + 3

Combine like terms: 3 + 3 = 6
1x = 6

Divide each side by '1'.
x = 6

Simplifying
x = 6

See similar equations:

| (3y-28)/7=y/3 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16t | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.6t | | 7x+(10)=3 | | (x-28)/7=y/3 | | -5(5x+3)=45 | | 30(c+4)=900 | | 21=x-87+2x | | -19.82+18.5b=-9(-3b-12.72) | | X+0.16X=9600 | | 9(x-3)+3=-15 | | (10+5)*(30+6)=15+36 | | -6x-7x+4=5 | | 21(n+22)=945 | | N-1-3=-1 | | 2m+4n=12 | | 7(7r+19)=7-14r | | 12x+3=-10 | | -8x+4x+6x=-6 | | -12x+2y=-14 | | 3(7h-15)=9+18h | | -7(7-3x)=-175 | | 16x+8=-3 | | q/8-5=9 | | -17w+7(17w+12)=18w | | 5x+2-6x=-11 | | 702/u=27 | | 18.94+15.8g=-3(-18.8g+11.28) | | a-42=-4a-7 | | 5(8+2x)=-30 | | -2x+4-2x=-12 | | 18.94-15.8g=-3(-18.8g+11.28) |

Equations solver categories